Dynamics of Small Solar System Bodies and Exoplanets - Souchay, Jean J.; Dvorak, Rudolf (Lecture Notes in Physics, 2010)
This book offers an up-to-date overview of current research on Dynamics of Small Solar System Bodies and Exoplanets. In course-tested extensive chapters the authors cover topics of theoretical celestial mechanics, physics and dynamics of asteroids, comets, stability of exoplanets and numerical integration codes applied in dynamical astronomy.